MATLAB software/code for optimal placement of GIPFC device in power networks using AALO algorithm - Mallala, Balasubbareddy (Software impacts, 2023)
MATLAB software is used for developing a proposed algorithm and finding the optimal location of the proposed FACTS device. Optimal power low (OPF) problems include many control parameters in the power system network. This paper proposed a novel Ameliorated Ant Lion Optimization (AALO) Algorithm. To improve the performance of the power system a novel hybrid FACTS device named a Generalized Interline Power Flow Controller (GIPFC) has been proposed. Optimal allocation of the proposed device a novel LSZ (Lehmann, Symanzik and Zimmermann) approach is used. Results of the IEEE 30 bus system are compared with existing literature. •MATLAB software code for a novel Ameliorated Ant Lion Optimization (AALO) Algorithm.•MATLAB software code for optimal location of Generalized Interline Power Flow Controller (GIPFC) in the power system.•Implications of LSZ (Lehmann, Symanzik and Zimmermann) formula for identifying the optimal location for GIPFC.•OPF problems for a single objective optimization for generation fuel cost minimization.